Easy r Engaging ESL Activities And Mini-Books For Every Classroom : Terrific teaching tips, games, mini books r more to help new student from every nation build basic english vocabulary and feel welcome! - Einhorn, Kama (Scholastic Professional Books, 2001)
63 p. : il.; 29 cm.